Hard Skill of Human Resource Enhances Innovation Individual Capability at Coffee Small Medium Entreprises - Fauziah, Hanifah; Hermina, Tinneke; Basit, Acep Abdul; Alkautsar, Muslim; Wufron, Wufron (Fakultas Ekonomi Universitas Garut, 2025)
The purpose is to analyze the effect of hard skills on innovation individual capabilities at coffee small and medium enterprises. Data collection was carried out by census sampling of 45 respondents at 17 coffee SMEs. The results of the questionnaire were returned and valid. Simple regression linear analysis used for data processing. The research results show that individual innovation capability among coffee SMEs in is influenced by hard skills. The ability to use software and the internet, utilize tools and equipment, as well as conceptual thinking, can trigger the implementation of innovations and problem-solving in coffee processing for coffee SMEs. Thus, the actor of coffee SMEs can enhance their hard skills, as these skills play a crucial role in supporting their success, innovation, and sustainable growth in this competitive and rapidly evolving industry.